CAPACITIVELY COUPLED RF PLASMA SOURCES - A VIABLE APPROACH FOR CVD DIAMOND GROWTH - Beckman, J; Jackman, R; Foord, J (1994)
The means by which microwave and r.f. excitation can stimulate gaseous plasma formation are considered in terms of the requirements for a diamond chemical vapour deposition (CVD) process. It is apparent that capacitively coupled r.f. plasma sources offer distinct practical advantages over microwaves but to date these have not been effectively used to grow good quality diamond. This is likely to be due to relatively high ion energy impacts on the growing film and low plasma densities. The addition of magnetic fields to such a source, along with a reconfigured electrode system may overcome these problems and offer a stable and relatively low cost CVD diamond source. Preliminary results are reported from a novel source configuration indicating that diamond can indeed be grown using this approach. © 1994.